2015
DOI: 10.1016/j.sbspro.2015.01.433
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Hybrid Fuzzy Multiple Criteria Decision-making Approach to Evaluating of QM Critical Success Factors in SME's Hotels Firms

Abstract: The purpose of this study is to evaluate the importance of QM CSFs in Iranian SME's hotels firms. Primary criteria to evaluate QM CSFs are achieved by the literature survey. Through the FDM by industries and academia experts the importance CSFs were categorized in three main factors and 16 sub-factors. Two fuzzy MCDM methods are applied; fuzzy AHP and TOPSIS. The finding of this study indicated that human factors had the first rank from three perspectives and leadership as a sub-factor was the first rank from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Literature indicates business operations as a very important CSF (Brotherton, 2004(a&b); Burger and Saayman, 2009;DiPietro et al, 2007;Jaafar, 2011;Hung, 2013;Mardani et al, 2015;Pikkemaat and Schuckert, 2007;) which includes constructs such as safety and security (Respondent 3 agrees with this), strategic control, hygiene, quality, pricing and organisational support, to name a few. In this case study, respondents 1 and 3 indicated that the management of the administration and finances were outsourced to other companies as constructs of this particular CSF of the business.…”
Section: Theme or Factor 3: Effective Business Operationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Literature indicates business operations as a very important CSF (Brotherton, 2004(a&b); Burger and Saayman, 2009;DiPietro et al, 2007;Jaafar, 2011;Hung, 2013;Mardani et al, 2015;Pikkemaat and Schuckert, 2007;) which includes constructs such as safety and security (Respondent 3 agrees with this), strategic control, hygiene, quality, pricing and organisational support, to name a few. In this case study, respondents 1 and 3 indicated that the management of the administration and finances were outsourced to other companies as constructs of this particular CSF of the business.…”
Section: Theme or Factor 3: Effective Business Operationsmentioning
confidence: 98%
“…These themes / factors are supported by literature as indicated next to each factor. The six themes / factors, not presented in any specific order of importance, are: Customer relations (Brotherton, 2004(a); Ferreira and Fernandes, 2015;Geller, 1985;Lin and Fu, 2012;Marais and Saayman, 2011;Van der Westhuizen, 2003;MacCarthy et al, 2006); Location (Brotherton, 2004(a); Camillo et al, 2008;Nieh and Pong, 2012;Wang and Hung, 2015); Effective operations (Brotherton, 2004(b); Burger & Saayman, 2009;DiPietro et al, 2007;Hung, 2013;Pikkemaat and Schuckert, 2007;Jaafar, 2011;Mardani et al, 2015;Wilks and Davis, 2000); Quality products and services (Engelbrecht et al, 2014;Geller, 1985;Getz and Brown, 2006;Williams and Soutar, 2009); Resources (Avcikurt et al, 2011;Choon-Chiang, 1998;Li et al, 2006;Wang et al, 2011); and Networks (Getz, 2003;Haven-Tang, Jones and Webb, 2007;Hamzah and Mohamad, 2012;Hua et al, 2009;Lucchetti andFont, 2013 Mohamed, 2015;Ortgueira and Gomez-Selemeneva, 2011).…”
Section: Question Five (Q5)mentioning
confidence: 99%
“…Chittithaworn et al [28] found the success factors of SMEs in Thailand. Mardani et al [29] evaluated the SME-scale hotels in Iran with three main factors and 16 sub-factors using AHP and TOPSIS. In their work, Johnes and Johnes [30] assessed the performance of the economic units in the UK using DEA.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The most representative example is the one publication (Fu, Chu, Chao, Lee & Liao, 2011) about AHP and VIKOR for benchmarking analysis in the hotel industry, but it is a comparison through 26 hotels in Taiwan with criteria of mainly economical interest. There are other recent publications which are related to a certain extent (Đorđević, Zecevic & Hristov, 2016;Akincilar & Dagdeviren, 2014;Lee & Lee, 2015;Mardani, Jusoh, Bagheri & Kazemilari, 2015;Shirouyehzad, Arabzad & Reza, 2013), however they are using AHP or VIKOR for research on other factors or they focus on one country. Therefore there seems to be a gap in the comparison of hotels between different countries, but with similar tourism characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%